PROSPECTS FOR STRENGTHENING THE QUALITY OF HUMAN CAPITAL : PROSPECTS FOR STRENGTHENING THE QUALITY OF HUMAN CAPITAL - Eskalieva, A.Zh.; Dariskalieva, M.S.; Kanatova, A.Zh. (Academic Journal of Physical and Chemical Sciences, 2018)
According to the authors, every year the quality of human capital increases and the share of specialists employed in the non-state sector of the economy increases. The increased competitive environment in the labor market pushes employers towards higher pay. In such conditions, private sector enterprises are forced to increase efficiency and productivity by using new technologies and equipment. The transition to market relations in the investment in human capital sector is accentuated by major consequences and leads, ultimately, to increased competition. Such predicted changes will create conditions for full-scale transformation. A new, emerging model of economic growth presupposes a new stage of reforms in higher education. They are able to awaken forces hidden in the human personality and determine the constituent features of human capital.